Language Learning and Language Universals - Jeffrey Lidz (Biolinguistics, 2010)
This paper explores the role of learning in generative grammar, highlighting interactions between distributional patterns in the environment and the innate structure of the language faculty. Reviewing three case studies, it is shown how learners use their language faculties to leverage the environment, making inferences from distributions to grammars that would not be licensed in the absence of a richly structured hypothesis space.